The relationship between self-regulated learning and learning motivation among working students - Mutia Mawardah; Umi Kalsyum (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2023)
This study aims to investigate the relationship between self-regulated learning of working students of Bina Darma University in Palembang and learning motivation. The hypothesis of the study was there is a relationship between self-regulated learning of working students of Bina Darma University in Palembang and learning motivation. This study was conducted using a quantitative method. The instruments used in the study were the self-regulated learning scale and the learning motivation scale. Purposive sampling was adopted and 500 staff members of Bina Darma University in Palembang were selected as the sample of the study. The data were analyzed using the SPSS program version 20 for Windows, resulting in a coefficient (r) of 0.516, a determination coefficient (R square) of 0.266, and the p value was 0.001 for the two-way ANOVA. The results of the study showed that the hypothesis that self-regulated learning was positively and significantly correlated to learning motivation of the working students of Bina Darma University in Palembang was valid.